The Dark Tetrad: Identifying personality profiles in high-school students. (September 2015) - Chabrol, Henri; Melioli, Tiffany; Van Leeuwen, Nikki; Rodgers, Rachel; Goutaudier, Nelly
Highlights: The "Dark Tetrad" of personality traits has received increasing attention. There is no typological study among high-school students based on these traits. Cluster analysis yielded four groups. The "Dark Tetrad" cluster constituted 15% of the total sample. Abstract: Psychopathic, narcissistic, Machiavellian, and sadistic traits constitute the Dark Tetrad of personality traits. While this construct has received increasing attention, to our knowledge, there is no typological study aiming to identify homogeneous groups of high-school students based on these traits. The aim of this study was (a) to identify a typology of high-school students based on the Dark Tetrad traits in a community sample and (b) to examine whether these profiles differ on psychopathological variables known to be associated with personality traits. Participants were 615 high-school students who completed self-report questionnaires. Psychopathic, narcissistic, Machiavellian, and sadistic traits were moderately correlated suggesting they may be overlapping but distinct constructs. Cluster analysis yielded four groups: a Low Traits group, a Sadistic–Machiavellian group, a Psychopathic–Narcissistic group, and a high traits group called the Dark Tetrad cluster which was high on all traits. The Dark Tetrad cluster constituted 15% of the total sample and was characterized by the highest levels of antisocial behaviors and suicidal ideations. This study suggests that a significant minority of non-clinical high-school students is characterized by the presence of high levels of the Dark Tetrad traits and self and other-aggression.